Design and control application of stepping motor for ventilating system - (:unkn) unknown (IEEE, 2007)
In this study a variable reluctance (VR) type step motor is operated under bipolar mode with microcontroller system to adjust the temperature of the ambient. As parts of primary study a controller system is designed and constructed to step motor. The microcontroller system is used to control the stepping motor. The system is simulated and operated to compare the results. Both studies have been executed successfully and results have been given in detail. This type of system is developed especially for what the sensitive temperature distribution is desired.
Keywords: step motor; microcontroller; ventilation system